Effect of assisted reproductive technology on multiple sclerosis relapses: Case series and meta-analysis. (October 2020) - Bove, Riley; Rankin, Kelsey; Lin, Chris; Zhao, Chao; Correale, Jorge; Hellwig, Kerstin; Michel, Laure; Laplaud, David A; Chitnis, Tanuja
Background: Five case series reported increased relapse risk after assisted reproductive technologies (ART) in women with multiple sclerosis (MS), but small numbers and heterogeneous study design limit broader conclusions. Objective: To evaluate the risk of relapses after ART in an independent case series and in aggregated analyses of existing studies. Methods: We compared annualized relapse rate (ARR) in the 3 months after, and 12 months before, ART in (1) an unpublished cohort (Boston: prospectively collected relapses; 22 ART cycles), (2i) data pooled from Boston and five published studies (164 cycles), and (2ii) a meta-analysis of all case series published by 2017 (220 cycles; PRISMA and MOOSE guidelines). Results: In the Boston cohort, mean ARR was not higher after ART than before (mean: 0.18 ± 0.85 vs 0.27 ± 0.55, p  = 0.58). In the pooled analyses, ARR was significantly higher after ART for all clinical scenarios, including varying ART protocols ( p  ⩽ 0.01 for each). The meta-analysis confirmed an increased ARR after ART (mean difference (MD) = 0.92, 95% confidence interval (CI) = [0.33, 1.51], p  = 0.01). Conclusion: These pooled data support an increase in ARR following ART. Reasons for local variation in ARR after ART, and consideration of MS treatments during conception attempts, will be pursued.